About the stability of Takagi–Sugeno uncertain singularly perturbed systems. The case of stable subsystems - Khoroshun, A. S. (Reports of the National Academy of Sciences of Ukraine, 2014)
The sufficient conditions of the asymptotic stability of a fuzzy model with parametric uncertainties are established. An appropriate scalar Lyapunov function is built. The region in the space of parameters, for which the mentioned type of stability holds, is found.